EFFECT OF SPROUTING ON IN-VITRO ANTIOXIDANT POTENTIAL OF SOME VARIETIES OF CHICKPEA SEEDS (CICER ARIETINUM LINN.) - Kaur, Jasneet; Singh, Satnam (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim of the present study is to access the effect of sprouting on in-vitro antioxidant potential of some varieties of Cicer aurantium Linn. (Chickpea seeds). Materials and Methods: The un-sprouted and sprouted seeds of its newly developed varieties viz. PBG-1, GPF-2, PBG-5 were powdered and then was extracted with methanol by direct maceration method and their antioxidant activity was evaluated using four different methods (Reducing power, Free radical scavenging activity (DPPH), total antioxidant activity and ferric reducing antioxidant power activity). Results: Sprouting clearly increased the flavonoid content of seeds to 104%, 117%, 341% respectively. There was visible increase in total antioxidant activity of methanol extracts of sprouted seeds which was evident by increased activity from 0.298 to 0.397 at concentration 60 µg/ml in var. PBG-5 and increased ferric reducing antioxidant power from 0.332 to 0.387 at concentration 40 µg/ml in var. PBG-1. Conclusion: Thus it may be concluded from the study that sprouting visibly increased the in-vitro antioxidant activity of selected chickpea seeds varieties.